Jan Kott is Dead, Long Live to the ˂“Hybrid”˃ Critic - Fedorova, Elizaveta Tsirina; Saiz Molina, Jose; Haba Osca, Julia (Multicultural Shakespeare: Translation, Appropriation and Performance, 2021)
This article is a little tribute that a drama teacher, an editor and translator and a lecturer in English Literature would like to contribute to this Special Issue in Honour of Professor Dr Jan Kott, the most influential non-English speaking Shakespearean Critic in the second half of the 20th Century and early 21st Century. In the initial part of the essay we will overview Kott’s influence in the development of current Shakespearean tradition(s) in Spain from the early 1970s to the present day. In fact, his writings and critical views on William Shakespeare’s Works have been a decisive point in the development of new approaches to this playwright in some University Departments and Drama Schools in this country. The whole discussion will take the notion of hybrid and hybridization as the point of departure and we will draw some conclusions for discussing new critical thinking in Art (Science,) and Humanities.